The sanctioning powers of regulatory agencies in Brazilian law: brief comments (Revista do Tribunal Regional Federal da 3ª Região, 2013)
This simple article aims to contribute in some way to a subject on which scholars have differing opinions or studies: the sanctioning powers of regulatory agencies. To this end, the subject is approached from a global and unitary perspective of the Law, but without going beyond the Brazilian Constitution. Therefore, some issues are analyzed from the perspective of the systematic interpretation of national law. Therefore, the focus of the work is on the possibility, or not, of applying the general lines of the US system to the national legal system, where regulatory agencies have spread the most. A distinction is made between the general supremacy and special supremacy of the state, which are the spheres of action of regulatory agencies. The difference in legal regime leads to relevant consequences. The conclusion is that regulatory agencies should be subject to the regime laid down in the Brazilian Federal Constitution and the country's laws. Of course, any criticism is aimed at the legal model, and not at the employees of the regulatory agencies.
Keywords: regulatory agencies; sanctioning power; special supremacy of the state; legal regime